Effects of redox oscillations on the phosphogypsum waste in an estuarine salt-marsh system. (March 2020) - Papaslioti, Evgenia-Maria; Pérez-López, Rafael; Parviainen, Annika; Phan, Van T.H.; Marchesi, Claudio; Fernandez-Martinez, Alejandro; Garrido, Carlos J.; Nieto, José M.; Charlet, Laurent
Abstract: Salt marshes are natural deposits of heavy metals in estuarine systems, where sulphide precipitation associated with redox changes often results in a natural attenuation of contamination. In the present study, we focus on the effects of variable redox conditions imposed to a highly-polluted phosphogypsum stack that is directly piled over the salt marsh soil in the Tinto River estuary (Huelva, Spain). The behaviour of contaminants is evaluated in the phosphogypsum waste and in the marsh basement, separately, in controlled, experimentally-induced oscillating redox conditions. The results revealed that Fe, and to a lesser extent S, control most precipitation/dissolution processes. Ferric iron precipitates in the form of phosphates and oxyhydroxides, while metal sulphide precipitation is insignificant and appears to be prevented by the abundant formation of Fe phosphates. An antagonistic evolution with changing redox conditions was observed for the remaining contaminants such as Zn, As, Cd and U, which remained mobile in solution during most of experimental run. Therefore, these findings revealed that high concentrations of phosphates inhibit the typical processes of immobilisation of pollutants in salt-marshes which highlights the elevated contaminant potential of phosphogypsum wastes on coastal environments. Highlights: Estuarine salt-marsh systems are geochemically controlled by redox conditions. In the Huelva Estuary, phosphogypsum wastes are deposited directly on salt marshes. The waste and the marsh soil geochemistry was simulated under redox oscillations. Fe-phosphate abundance hinders sulphide formation and contaminants' immobilisation. Natural attenuation is impeded, leading to high pollution risk to the environment.